High-resolution 3D-GRE imaging of the abdomen using controlled aliasing acceleration technique - a feasibility study. - AlObaidy, Mamdoh; Ramalho, Miguel; Busireddy, Kiran; Liu, Baodong; Burke, Lauren; Altun, Ersan; Dale, Brian; Semelka, Richard; Busireddy, Kiran K R; Burke, Lauren M; Dale, Brian M; Semelka, Richard C (European Radiology, 2015)
Objectives: To assess the feasibility of high-resolution 3D-gradient-recalled echo (GRE) fat-suppressed T1-weighted images using controlled aliasing acceleration technique (CAIPIRINHA-VIBE), and compare image quality and lesion detection to standard-resolution 3D-GRE images using conventional acceleration technique (GRAPPA-VIBE).Materials and Methods: Eighty-four patients (41 males, 43 females; age range: 14-90 years, 58.8 ± 15.6 years) underwent abdominal MRI at 1.5 T with CAIPIRINHA-VIBE [spatial resolution, 0.76 ± 0.04 mm] and GRAPPA-VIBE [spatial resolution, 1.17 ± 0.14 mm]. Two readers independently reviewed image quality, presence of artefacts, lesion conspicuity, and lesion detection. Kappa statistic was used to assess interobserver agreement. Wilcoxon signed-rank test was used for image qualitative pairwise comparisons. Logistic regression with post-hoc testing was used to evaluate statistical significance of lesions evaluation.Results: Interobserver agreement ranged between 0.45-0.93. Pre-contrast CAIPIRINHA-VIBE showed significantly (p < 0.001) sharper images and lesion conspicuity with decreased residual aliasing, but more noise enhancement and inferior image quality. Post-contrast CAIPIRINHA-VIBE showed significantly (p < 0.001) sharper images and higher lesion conspicuity, with less respiratory motion and residual aliasing artefacts. Inferior fat-suppression was noticeable on CAIPIRINHA-VIBE sequences (p < 0.001).Conclusion: High in-plane resolution abdominal 3D-GRE fat-suppressed T1-weighted imaging using controlled-aliasing acceleration technique is feasible and yields sharper images compared to standard-resolution images using standard acceleration, with higher post-contrast image quality and trend for improved hepatic lesions detection.Key Points: • High-resolution imaging of the upper abdomen is clinically feasible using 2D-controlled aliasing acceleration technique. • High-resolution imaging yields significantly sharper images and increased hepatic lesions conspicuity. • High-resolution imaging yields significantly less respiratory motion and residual aliasing artefacts. • Controlled-aliasing offers substantial acquisition-time reduction in patients with breath-holding difficulties.